Adsorption of lubricity improver additives on sliding surfaces. (January 2020) - Shaigan, Nima; Neill, W. Stuart; Littlejohns, Jennifer; Song, Datong; Lafrance, Simon
Abstract: Lubricity improver additives are adsorbed on sliding surfaces and form boundary films. Although for most additives, the films are monolayers, multilayer adsorption does occur in tribological contacts. However, to date, the isotherms adopted to study the adsorption thermodynamics for tribological systems are limited to monolayer films. To address this, the original Brunauer–Emmett–Teller (BET) gas adsorption isotherm was modified for use in dilute liquid solutions. The modified BET isotherm was used to fit experimental wear data collected using high frequency reciprocating rig (HFRR) for ultra-low sulphur diesel (ULSD) fuels containing trace levels of commercial lubricity improving additives. The results suggested that for certain additives in ULSD, the boundary film is multilayer. Highlights: Adsorbed films in boundary lubrication condition may be multilayer. A modified Brunauer–Emmett–Teller (BET) isotherm explains multilayer films. The modified BET isotherm fits the experimental wear data. This isotherm suggests multilayer film adsorption occurs in boundary lubrication.